UTILIZATION OF MOODLE WEB SERVICE BASED SYSTEM TO SYSTEM WITH SIAKAD AND SSO UNS - Ristu Saptono; Meianto Eko Sulistyo; Joko Susilo (Telematika, 2016)
The development of information technology in education allows for integration between systems so every system can be optimized. Elearning, SIAKAD, and SSO UNS are education system in UNS (Universitas Sebelas Maret) but they are not integrated yet. Course data for elearning is still manual and SSO which can not be used to log into SIAKAD. In this study the integration of elearning, SIAKAD, and SSO utilizing REST web service and exchange data using JSON. As a result, the integration of additional system must use a bridge application as a customizer data between elearning and SIAKAD. While the results of the testing to include one course, 40 lecturers, and 40 students, including automatically enroll is 60.22 seconds, while the time required for unenroll lecturers and students is 2:13 seconds. To enroll course, lecturers and students when there are previously data was 28.5 seconds.